Dampak Permainan Olahraga Tradisional dalam Menanamkan Perilaku Sosial - Mudayat Mudayat (Pusat Riset dan Inovasi Nasional, 2025)
Humans are social beings where social behavior must be instilled early on or at elementary school level, when children enter elementary school their social behavior with others will be seen, this is because before entering elementary school children are in a community environment that influences children's social behavior in a negative direction so that it is carried over to their school environment. Such as fighting with friends, isolating friends, saying dirty words, inciting friends in a bad direction. One way to instill social behavior in children is through traditional sports games, because in traditional sports games it requires communication, and cooperation between individuals which may have an impact on children's social behavior. This study uses a descriptive qualitative approach with teachers and students as research subjects, this study was conducted in 4 Elementary Schools in Mataram Baru Village, Mataram Baru District, East Lampung Regency. Because these schools are based on learning that forms their students to have good behavior, the subjects in this study were the principal, student representatives, class teachers, physical education teachers or instructors and students. The data collection techniques used were observation, interviews and documentation. While data analysis through three techniques, namely data reduction, data presentation, and drawing conclusions. And checking the validity of the data is done by triangulation and source triangulation.